Selective Hemorrhoidal Dearterialization with High Mucopexy in the Surgical Treatment of Hemorrhoidal Disease - Rotta,Carlos Mateus (2021)
Abstract The doppler-guided transanal hemorrhoidal dearterialization technique associated with mucopexy is a noninvasive surgical option used to treat hemorrhoidal disease (HD). Objective To compare and analyze the results using a variation of the doppler-guided transanal hemorrhoidal dearterialization technique with the technique of selective hemorrhoidal dearterialization with high mucopexy in the treatment of HD. Method A total of 292 patients who underwent surgical treatment for grade II, III and IV HD from March 2012 to December 2017 were studied. From this total, 110 (37.6%) patients underwent a conventional doppler-guided transanal hemorrhoidal dearterialization with mucopexy (CD), and 182 (62.3%) underwent selective hemorrhoidal dearterialization with highmucopexy (SHeLF). In the group of patients undergoing CD, 4 patients (3.64%) had grade II HD, 82 (74.55%) grade III, and 24 (21.82%) grade IV. In the group submitted to SHeLF, 18 (9.89%) patients had grade II HD, 86 (47.25%) had grade III, and 65 (35.71%) had grade IV. The same surgeon operated all patients under spinal anesthesia. In patients undergoing CD, six arterial branches have been dearterialized, while in patients undergoing SHeLF, the hemorrhoidary nipples submitted to a dearterialization were selected (from 1 to 5) by intraoperative evaluation followed by high rectal mucopexy. In the postoperative period, the following parameters were evaluated: pain, tenesmus, bleeding, and recurrence. Moderate results to severe pain was a postoperative complaint reported by 13 (11.82%) patients undergoing CD, and by 19 (10.44%) undergoing SHeLF. Intense tenesmus was reported by 26 (23.64%) patients undergoing CD and by 7 (3.85%) undergoing SHeLF. Three patients (2.73%) undergoing CD and 1 (0.55%) undergoing SHeLF evolved with postoperative bleeding. One patient (0.55%) in the group undergoing CD required surgical review of hemostasis. Six patients (5.45%) who underwent CD and 8 (4.39%) who underwent SHeLF were reoperated due to disease recurrence. Conclusion Comparing statistics, patients undergoing the SHeLF technique have less postoperative pain, tenesmus and postoperative bleeding when compared with CD.